Model Sistem Informasi Penyewaan Mobil Wibi Rent Car Berbasis Web Mobile - Alifan Purnomo Aji; Edy Supriyanto (STMIK Banjarbaru, 2023)
The car rental administration system that runs at Wibi Rent Car is not yet effective because it is still carried out using a manual recording system. This study aims to develop a Web-based information system model that can be used to assist business management in managing data collection, product promotion, and managing car rental activities as well as online management reporting. System development follows the general stages of the Prototype method. The system design uses object-oriented tools, while the implementation uses the PHP programming language with the Laravel framework and MySQL database. Functional features for car registration, tenant data, driver data, promotions and online rental transactions, as well as management reporting are validated using Blackbox Testing. The test results show that the functional features are running validly.Keywords: Car rental; Web-based system; Prototype Method; Laravel Framework; Blackbox testing AbstrakSistem administrasi penyewaan mobil yang berjalan di Wibi Rent Car belum efektif karena masih dilakukan menggunakan sistem pencatatan manual. Penelitian ini bertujuan untuk mengembangkan model sistem informasi berbasis Web yang dapat digunakan untuk membantu manajemen usaha dalam melakukan manajemen pendataan, promosi produk, dan mengelola aktivitas penyewaan mobil serta pelaporan manajemen secara online. Pengembangan sistem mengikuti tahapan-tahapan umum dalam metode Prototype. Desain sistem menggunakan tools berorientasi objek, sedangkan implementasi menggunakan bahasa pemrograman PHP dengan framework Laravel dan database mySQL. Fitur-fitur fungsional untuk pendataan mobil, pendataan penyewa, pendataan pengemudi, promosi dan transaksi penyewaan secara online, serta pelaporan manajemen divalidasi menggunakan Blackbox Testing. Hasil uji menunjukkan fitur-fitur fungsional telah berjalan secara valid.